Post-mortem toxicogenetics: determining the suitable of blood samples collected for routine toxicological analyses for use in subsequent genetic analyses - Vuko, Loyiso Abongile Marvin (Division of Forensic Medicine and Toxicology, 2019)
South Africa has one of the highest prevalences of drug misuse and abuse in Africa. Salt River Mortuary (Cape Town, South Africa), along with other national Forensic Pathology Service providers, receives many cases of suspected drug-related deaths. In some cases, the traditional autopsy – when viewed together with the decedent's history – is not able to indicate whether a drug-related death is accidental or suicidal in relation to altered drug metabolism. Literature has shown that this can be investigated by sequencing gene(s) encoding the implicated metabolising enzyme(s) in a postmortem genetic analysis. However, as such an analysis would normally be performed following the obtainment of postmortem toxicological results, it is imperative to investigate whether blood samples retrieved back from a toxicology laboratory would be sufficient for the said genetic analysis, despite the handling involved in the process of toxicological investigation. To this end, blood samples from 30 deceased individuals in which drug use/abuse may have contributed to death, were collected into two red-top tubes (plain), two grey-top tubes (containing sodium fluoride and potassium oxalate) and one EDTAcontaining purple-top tube (control). DNA was immediately extracted from one of each colour tube, while the duplicate red-top and grey-top tubes first underwent a process of toxicological analyses, and then underwent DNA extraction. The concentration, degradation, purity, contamination, and quality of DNA were assessed using real-time PCR, spectrophotometry, forensic DNA profiling, and Sanger sequencing. In contrast to the grey-top tubes, the results showed that the red-top tubes were most suitable for the aforementioned genetic analysis. Overall, the study not only demonstrated that postmortem genetic analysis using samples retrieved from a toxicology laboratory is possible in the local context, but also provided guidelines around the pre-analytical phase of the analysis. These results illustrate the opportunity to investigate these toxicogenetic avenues further, particularly in future expansion of services currently provided at Salt River Mortuary, which may provide families more information about circumstances of their relative’s death.